Transcatheter Bioprosthetic Aortic Valve Dysfunction: What We Know So Far - Sawaya, Fadi; Jørgensen, Troels H.; Søndergaard, Lars; De Backer, Ole (Frontiers in Cardiovascular Medicine, 2019)
Transcatheter aortic valve replacement (TAVR) is an established alternative to surgical valve replacement for patients with severe aortic stenosis (AS) and increased surgical risk. On the basis of the favorable outcomes of recent randomized clinical trials conducted in intermediate and low risk populations, TAVR is expected in the near future to be offered to patients not only at lower surgical risk, but also with longer life expectancy. In this particular subset, the long-term durability of the bioprosthetic valve is of critical importance. The European Association of Percutaneous Cardiovascular Interventions (EAPCI), the European Society of Cardiology (ESC), and the European Association for Cardio-Thoracic Surgery (EACTS) recently introduced standardized criteria to define structural valve deterioration (SVD) and valve failure of transcatheter and surgical aortic bioprosthesis—this with the aim to generate uniformity in data reporting in future studies assessing long-term durability of aortic bioprosthesis. On this background, the aim of this article is to review the definition, incidence and predictors of transcatheter bioprosthetic valve dysfunction, including structural and non-structural valve deterioration (SVD/NSVD), valve thrombosis, and endocarditis.